Comparación de metodologías ágiles (XP y SCRUM) para la estandarización del proceso de desarrollo de software en la empresa “CloudStudio Compañía Limitada” - Guamán Siguenza, Janneth Patricia (2023)
This Degree Project aims to compare agile methodologies (XP and Scrum) to standardize the software development process within CloudStudio Compañía Limitada. This research focuses on agile methodologies such as XP (eXtreme Programming) and Scrum, which have strengthened frameworks for various organizations, prioritizing software quality in deliverables and adaptive planning for changes that may arise during the software development stage. Besides, the research applied methodologies, such as documentary research, to develop the scientific foundation by obtaining reliable information from scientific journals and books that contribute to and support the research topic. In addition to surveys to learn about the software development process within CloudStudio Cía. Ltd. The framework proposed in this research is a combination of the Scrum and XP methodologies since, according to the approaches of the characteristics of each methodology, it is possible to identify that each of them has different orientations and purposes; On the one hand, Scrum handles the administrative aspects of a software project, while XP is focused on handling the technical aspects. In this way, correctly defining the roles, meetings, and deliverable artifacts helps keep the projects or tasks to be carried out within the work team organized effectively, obtaining general planning and control of the tasks so that those involved can visualize the project status. Applying the proposed framework in this research results in complete satisfaction for the development team members of the company CloudStudio Cía. Ltda., since in its implementation, they shared teamwork experiences. Finally, it is necessary to emphasize; agile Scrum or XP methodologies can benefit companies significantly. However, it will always depend on the context in which they are applied and if their principles are well applied. Keywords: Agile Methodologies, Scrum, Extreme Programming, XP